2021
DOI: 10.1021/acsnano.1c03050
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast, Kinetically Limited, Ambient Synthesis of Vanadium Dioxides through Laser Direct Writing on Ultrathin Chalcogenide Matrix

Abstract: Vanadium dioxide (VO2) is a strongly correlated electronic material and has attracted significant attention due to its metal-to-insulator transition and diverse smart applications. Traditional synthesis of VO2 usually requires minutes or hours of global heating and low oxygen partial pressure to achieve thermodynamic control of the valence state. Further patterning of VO2 through a series of lithography and etching processes may inevitably change its surface valence, which poses a great challenge for the assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…[63] This synthetic strategy without complex equipment broaden the way in preparing 2D metal oxides semiconductor materials. [158][159][160][161] Subsequently, a liquid metal-based reaction route had been exploited to synthesize 2D materials including Ga 2 O 3 , [162][163][164] GaN, [28,72] Bi 2 O 3 , [165] PbO, [166] SnO, [145] ITO, [146] IZO, [118] β-TeO 2 , [66] SnO, [145] ZnO, [113] V 2 O 5 , [167] SnO 2 , [126] and ZnO. [147] Recently, Daeneke' group reported a modified liquid metal roll-printing technique for synthesis 2D p-type β-TeO 2 nanosheet.…”
Section: Top-down Methodsmentioning
confidence: 99%
“…[63] This synthetic strategy without complex equipment broaden the way in preparing 2D metal oxides semiconductor materials. [158][159][160][161] Subsequently, a liquid metal-based reaction route had been exploited to synthesize 2D materials including Ga 2 O 3 , [162][163][164] GaN, [28,72] Bi 2 O 3 , [165] PbO, [166] SnO, [145] ITO, [146] IZO, [118] β-TeO 2 , [66] SnO, [145] ZnO, [113] V 2 O 5 , [167] SnO 2 , [126] and ZnO. [147] Recently, Daeneke' group reported a modified liquid metal roll-printing technique for synthesis 2D p-type β-TeO 2 nanosheet.…”
Section: Top-down Methodsmentioning
confidence: 99%
“…[ 16 ] However, the researchers have found that the electric field has obvious obstacles, such as single function, weakness expansion, and device vulnerability, even though it is facile to control. [ 33 , 34 , 35 , 36 , 37 , 38 ] To extend the application of the memristors, additional external stimuli are introduced, such as magnetic field, [ 39 , 40 , 41 , 42 , 43 ] temperature, [ 44 , 45 ] external pressure, [ 46 ] etc. In particular, these stimuli are orthogonal with the electric field when operating the memristor.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common lasers, carbon dioxide (CO 2 ) laser has been widely used in food, medicine, machinery and electronics, aerospace, and other fields with the characteristics of low-cost, simple operation, and high photothermal conversion efficiency. The interaction between CO 2 laser and materials is mainly manifested as the thermal effect, which can be used in the surface treatment, cutting, patterning, and perforation of materials. Recently, laser direct writing (LDW) as new technology has been widely used for the surface patterning of metals, ceramics, plastics, and other materials. LDW exhibits great potential in designing patterns, especially for polymers, in that the high-energy laser beam irradiates the materials to generate instantaneous high temperature, leaving permanent patterns on the polymers’ surface by carbonization, discoloration, vaporization, or foaming. Typical applications are to make logos, images, texts, two-dimensional codes, or barcodes to ensure the identification and traceability of various commodities.…”
Section: Introductionmentioning
confidence: 99%